2021
DOI: 10.1097/ico.0000000000002888
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Corneal Biomechanical Properties After Small-Incision Lenticule Extraction and Photorefractive Keratectomy, Using a Noncontact Tonometer

Abstract: Purpose:The aim of this study was to evaluate and compare early corneal biomechanical changes after small-incision lenticule extraction (SMILE) and photorefractive keratectomy (PRK).Methods:The study comprised 74 patients eligible for refractive surgery, equally allocated to PRK (37 patients) and SMILE (37 patients). Corneal biomechanical properties were recorded and compared between the 2 groups at preoperatively and 3 months after surgery using a dynamic ultra-high-speed Scheimpflug camera equipped with a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
2
0
1
Order By: Relevance
“…There is still controversy regarding whether different corneal ap thicknesses affect the Corvis ST Biomechanical Index (CBI). Different corneal ap thicknesses may lead to differences in corneal CBI and stiffness parameters at rst applanation 37 . Fang et al found no in uence of different ap thicknesses on CBI after SMILE, while another study showed signi cant differences in CBI and stiffness parameters at rst applanation between 110 µm cap and 145 µm cap 38 .…”
Section: Discussionmentioning
confidence: 99%
“…There is still controversy regarding whether different corneal ap thicknesses affect the Corvis ST Biomechanical Index (CBI). Different corneal ap thicknesses may lead to differences in corneal CBI and stiffness parameters at rst applanation 37 . Fang et al found no in uence of different ap thicknesses on CBI after SMILE, while another study showed signi cant differences in CBI and stiffness parameters at rst applanation between 110 µm cap and 145 µm cap 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Zarei-Ghanavati et al 43 estudiaron 74 pacientes, 37 sometidos a SMILE y 37 a PRK, y concluyeron que ambos procedimientos alteran significativamente las propiedades biomecánicas de la córnea; sin embargo, los cambios eran más prominentes después de SMILE.…”
Section: Corvis St En Cirugía Ocularunclassified
“…[2][3][4][5][6] Although the ability of the corneal flap to preserve the biomechanical strength of the cornea is substantially weakened after laser-assisted in situ keratomileusis (LASIK), the corneal cap has previously been shown to continue to play a role in maintaining the corneal biomechanics after SMILE. 7 It has been hypothesized that a thicker cap will result in the extraction of a deeper lenticule in the corneal tissue, maintaining more of the anterior portion of the cornea, which is biomechanically stronger than the posterior lamella and therefore offer biomechanical advantages. 2,8 Limited clinical studies have evaluated the outcomes of SMILE with different cap thicknesses (brief mention of results).…”
mentioning
confidence: 99%